Social context of educational failure of students - G. E. Zborovsky; P. A. Ambarova (Образование и наука)
Introduction. The article considers the educational failure of students as a social problem. Its relevance is due to the growth of educationally unsuccessful students and the need to overcome this phenomenon.The aim of the present article was to analyse the nature of the influence of the social context on the educational failure of students.Methodology and research methods. The research is based on the interdisciplinary methodology, which integrates the principles of sociological, psychological, socio-psychological, economic, and pedagogical approaches in the study of educational failure and ways to overcome it. The empirical basis of the article is the results of an interdisciplinary study using a qualitative mix strategy (2019–2020). The following methods were employed: semi-formal expert interviews, focus groups with school, college and university students, and the analysis of essays by high school students.Results and scientific novelty. The novelty of the research consists in the interpretation of educational failure, its social context, and in showing the limitations of the educational approach to the analysis of the phenomenon under consideration. The main results presented in the article involve the interpretation of educational failure as an educational and social phenomenon and its social context; the characteristics of the main contextual factors, which are analysed as social inequality in education, educational policy, the place of education in the system of social values and in the model of social success. The results of the empirical research reveal the understanding of educational failure as a social phenomenon, its social causes. It is concluded that the modern social context of Russian education limits the possibility of overcoming this phenomenon and needs to be changedPractical significance of the article is the possibility to take into account the results of the research to improve social technologies for overcoming educational failure.